Scientific agenda for climate risk and impact assessment of West African cropping systems - Diancoumba, Madina; MacCarthy, Dilys Sefakor; Webber, Heidi; Akinseye, Folorunso M.; Faye, Babacar; Noulèkoun, Florent; Whitbread, Anthony M.; Corbeels, Marc; Worou, Nadine (Elsevier, 2023)
Rainfed agriculture is at the centre of many West African economies and a key livelihood strategy in the region. Highly variable rainfall patterns lead to a situation in which farmers’ investments to increase productivity are very risky and will become more risky with climate change. Process-based cropping system models are a key tool to assess the impact of weather variability and climate change, as well as the effect of crop management options on crop yields, soil fertility and farming system resilience and widely used by the West African scientific community. Challenges to use are related to their consideration of the prevailing systems and conditions of West African farms, as well as limited data availability for calibration. We outline here a number of factors need to be considered if they are to contribute to the scientific basis underlying transformation of farming systems towards sustainability. These include: capacity building, improved models, FAIR data, research partnerships and using models in co-development settings.